POLICY WITHOUT EFFECT? ANALYSIS OF THE IMPLEMENTATION OF THE LIQUOR PROHIBITION REGULATION IN JAYAPURA CITY - Ibrahim Kristofol Kendi (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes the implementation of Regional Regulation Number 8 of 2014 on the Prohibition of Alcoholic Beverages in Jayapura City, which, after a decade of enforcement, has been assessed as having failed to produce significant social impacts. Although the policy aims to reduce crime, maintain public order, and protect younger generations, empirical evidence indicates that the circulation and consumption of alcoholic beverages remain high and are strongly correlated with criminal activities. This research employs a qualitative approach using a policy case study design, based on secondary data analysis from government documents, police reports, media coverage, and previous studies. The analysis applies the policy implementation models of Van Meter and Van Horn as well as Mazmanian and Sabatier, enriched by the street-level bureaucracy perspective and a socio-cultural approach. The findings reveal that implementation failure is driven by weak policy communication, limited resources, low commitment among implementers, poor inter-agency coordination, and social resistance resulting from the policy’s misalignment with local cultural values and economic conditions in Papua. Policy enforcement tends to be symbolic and selective, influenced by political and economic interests. Theoretically, these findings partially falsify classical policy implementation models and confirm the relevance of Grindle’s approach, which emphasizes power relations and competing interests. Future research agendas should focus on examining alternative policy options beyond total prohibition, conducting longitudinal analyses of social policy impacts, exploring the discretionary practices of frontline officials, and developing and testing implementation models based on community support and local cultural contexts.